Kościół Jezusa Chrystusa Świętych w Dniach Ostatnich w Polsce. - Kucharska, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Is Poland open to new religions? The answer to this question is a complex one. From the legal point of view every denomination or religion is guaranteed equality. However, when we consider that 90% of Poles are Roman Catholics (at least in statistics), we should note that Catholicism decidedly prevails and the remaining denominations are far from popular. Reaching back in history to the year 966, the Catholic faith has become a part of Polish culture over the centuries. Irrespective of the schisms the Church has experienced in the West, it has remained rather homogeneous in Poland. Yet its strong position has not hindered the representatives of other denominations in reaching Polish territories and winning over believers.